Uniform Energy Decay Rates for the Fuzzy Viscoelastic Model with a Nonlinear Source - Fengyun Zhang (Journal of Mathematics)
This paper considers the fuzzy viscoelastic model with a nonlinear source utt+Lu+∫0tgt−ζΔuζdζ−uγu−ηΔut=0 in a bounded field Ω. Under weak assumptions of the function gt, with the aid of Mathematica software, the computational technique is used to construct the auxiliary functionals and precise priori estimates. As time goes to infinity, we prove that the solution is global and energy decays to zero in two different ways: the exponential form and the polynomial form.